The traditional custom of Tawas Jaa as a means of strengthening social cohesion among the Dayak Deah community - Dewicca Fatma Nadilla; Bambang Subiyakto; Deasy Arisanty; Syaharuddin Syaharuddin; Fitri Mardiani; Ilham Galih Pambudi (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
The Tawas Jaa tradition practiced by the Dayak Deah community in Upau represents a culturally significant ritual imbued with profound spiritual and social values. Beyond its role as a medium of ancestral veneration, this tradition is an integral mechanism for reinforcing communal bonds. The collective participation of all societal strata in the ritual across gender, generational, and religious lines reflects a strong foundation of social cohesion rooted in shared religious and cultural beliefs. This study examines the sociocultural meaning of the Tawas Jaa tradition as a form of religious-based social cohesion within the Dayak Deah community of Kaong. Employing a qualitative research design with a descriptive approach, the research was conducted in Kaong Village, identified in 2024 & 2025 as the sole remaining village in the Upau subdistrict actively maintaining the Tawas Jaa practice. Data was collected through participant observation and in-depth interviews, with informants selected via snowball sampling techniques. Data analysis employed source triangulation, encompassing data reduction, data display, and conclusion drawing. The research findings indicate that the Tawas Jaa tradition serves as a central pillar of community cohesion, facilitating the integration of diverse social segments through collective involvement. The ritual encompasses elements of mutual cooperation, community-driven fundraising, and the symbolic use of cultural artifacts such as ancak and the dragon boat—each reinforcing collective identity and interdependence. In addition to its spiritual dimensions, the tradition underscores the importance of egalitarianism, social solidarity, and communal self-reliance. Furthermore, by embracing religious plurality, the tradition fosters a resilient social structure and affirms the enduring relevance of ancestral values in shaping communal life.     Tradisi Adat Tawas Jaa pada masyarakat Dayak Deah di Upau merupakan praktik budaya yang tidak hanya sarat nilai spiritual dan sosial, tetapi juga berfungsi sebagai sarana memperkuat kohesi sosial berbasis religi di tengah kehidupan komunitas. Tradisi ini tidak hanya menjadi bentuk penghormatan terhadap leluhur, tetapi juga menjadi sarana mempererat hubungan antaranggota komunitas. Melalui pelaksanaan ritual-ritual yang melibatkan seluruh elemen masyarakat, Tawas Jaa mencerminkan kohesi sosial yang berakar pada nilai-nilai religi yang kuat. Penelitian ini bertujuan mengeksplorasi makna tradisi adat Tawas Jaa sebagai bentuk kohesi sosial berbasis religi bagi masyarakat Dayak Deah Kaong. Metode penelitian yang digunakan kualitatif dengan pendekatan deskriptif. Dipilihnya Desa Kaong karena pada tahun 2024 & 2025 merupakan satu-satunya desa yang menyenggarakan Tradisi Adat Tawas Jaa ini di Kecamatan Upau. Data dikumpulkan dari observasi dan wawancara mendalam. Penentuan sampel dilakukan dengan teknik Snowball Sampling. Analisis data menggunakan teknik triangulasi sumber, melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan Tradisi Tawas Jaa dalam masyarakat Dayak Deah berfungsi sebagai pilar kohesi sosial, mengintegrasikan seluruh lapisan masyarakat melalui partisipasi lintas gender, generasi, dan agama dalam penyelenggaraan nya. Ritual ini melibatkan gotong royong, pengumpulan dana secara mandiri, serta simbol-simbol adat seperti ancak dan perahu naga yang memperkuat identitas budaya mereka. Selain nilai spiritual, Tawas Jaa juga menegaskan pentingnya kesetaraan, solidaritas sosial, dan kemandirian komunitas. Dengan menghormati keberagaman keyakinan, tradisi ini membangun ketahanan sosial dan komitmen terhadap nilai-nilai kolektif yang diwariskan oleh para leluhur.